Spatially-multiplexed fibre-optic bragg grating strain and temperature sensor system based on interferometric wavelength-shift detection - Kalli, Kyriacos; Jackson, David A.; Webb, David J.; Rao, Yunjiang; Brady, Garret P.; Zhang, Lin; Bennion, Ian (My University, 1995)
A prototype fibre-optic system using interferometric wavelength-shift detection, capable of multiplexing up to 32 fibre-optic Bragg grating strain and temperature sensors with identical characteristics, has been demonstrated. THS system is based on a spatially multiplexed scheme for use with fibre-based low-coherence interferometric sensors, reported previously. Four fibre-optic Bragg grating channels using the same fibre grating have been demonstrated for measuring quasi-static strain and temperature.
Keywords: Bragg gratings; Fiber optics; Diffraction gratings; Multiplexing; Interferometry